End‐of‐life care research on people with intellectual disabilities: Challenges for proactive inclusion in an Irish context. (17th December 2018) - Cithambaram, Kumaresan; Duffy, Mel; Courtney, Eileen
Accessible Summary: People with intellectual disabilities are living longer than ever before. Although people with intellectual disabilities are living longer, they still suffer from many illnesses. This may reduce their lifespan, and they may die earlier than other people and therefore require good end‐of‐life care whatever age they die. Views and opinions of people with intellectual disabilities are important in determining what is good care at the end of life. Ethical and practical guidelines in relation to recruitment, obtaining consent, and having conversation around sensitive issues are clearly discussed in this paper. Abstract: Background: In recent times, people with intellectual disabilities are increasingly included in research studies; however, their participation in sensitive research such as palliative and end‐of‐life care is less frequent. The reasons for not including people with intellectual disabilities in these kinds of research studies are issues in relation to obtaining consent, difficulty of recruiting, and engaging and collecting relevant information. This paper aimed to provide insight into how people with intellectual disabilities could be proactively included in research which is sensitive to their unique needs. Method: This study included 13 people with mild and moderate intellectual disabilities and explored their end‐of‐life care needs from their perspectives. After obtaining appropriate ethical approval, the research process was commenced. Applying the constructive grounded theory approach, data were collected and analysed by using the constant comparative method. A story from the book Am I Going to Die was used to enhance the understanding of the concepts of death and dying while collecting data. Findings: Participants with intellectual disabilities were recruited by establishing a close relationship with service providers. Capacity to consent and informed consent were fostered by carefully explaining the research process through easy‐to‐read information, and the data collection process was successfully completed by having a person‐centred approach. Conclusion: People with intellectual disabilities can be successfully included in research. This is possible when their diverse needs are carefully considered, and appropriately developed protocols which meet their needs in relation to their capacities and abilities are utilised. This approach requires a flexible and inclusive research process.